(untitled) (Моделювання, керування та інформаційні технології, 2025)
The convergence of artificial intelligence (AI), quantum computing, and neuromorphic systems represents a significant paradigm shift in the field of cybersecurity. This transformation is driven by the increasing complexity of cyber threats and the need for more sophisticated defense mechanisms. As cyber threats evolve, traditional security measures are often inadequate, necessitating the integration of advanced technologies such as AI and quantum computing to enhance cybersecurity frameworks.